Wariantywność (orto)graficzna pożyczek angielskich w świetle normatywistyki języka rosyjskiego - Romanik, Anna (Studia Rossica Posnaniensia, 2019)
The article focuses on the problem of orthographic and graphic variants of English loanwords in modern Russian. The empirical material was excerpted from normative dictionaries and Russian glossy magazines. The main purpose of the studies was to define the reasons for different notation of anglicisms, to illustrate the types of orthographic and graphic variants, and also to indicate the most important issues of loanword codification in normative practice. Variation in writing is a dynamic phenomenon in Russian (ortho) graphy that requires lexicographical description as there are no separate rules of notation for loanwords.